+10

1 year ago

Mathematics

High School

Answer:

17

Step-by-step explanation:

let the two numbers be X and Y

let larger number = Y

from the first statement

Y - X = 9 equation (1)

from the second statement

Y = 1+ 2X equation (2)

substitute equation (2) into (1)

1+2X-X = 9

1+X= 9

X = 9-1 = 8

X= 8

put X = 8 into equation (2)

Y= 1+2X

Y= 1+2(8)

Y= 1+16 = 17

larger number = 17.

Forgot your password?

Don't have an account? Sign up!

or go back to login page

Answer:17

Step-by-step explanation:let the two numbers be X and Y

let larger number = Y

from the first statement

Y - X = 9 equation (1)

from the second statement

Y = 1+ 2X equation (2)

substitute equation (2) into (1)

1+2X-X = 9

1+X= 9

X = 9-1 = 8

X= 8

put X = 8 into equation (2)

Y= 1+2X

Y= 1+2(8)

Y= 1+16 = 17

larger number = 17.